The Role of Midwives in Reproductive Health Education as an Effort to Delay Early Marriage Among Adolescents at the Dambalo Community Health Center - Fitriana Sain; Reny Retnaningsih (Jurnal Siti Rufaidah, 2025)
Early marriage is a reproductive health issue that remains a challenge in various regions of Indonesia, requiring effective educational interventions for adolescents. This study aims to analyze the role of midwives in reproductive health education as an effort to delay early marriage among adolescents at the Dambalo Community Health Center (UPTD Puskesmas Dambalo). The study used an analytical observational design with a cross-sectional approach and involved 30 adolescents selected through total sampling. The variables examined included the role of midwives, knowledge, attitudes, and intentions to delay marriage. Data were collected through a standardized questionnaire and analyzed using Spearman's and Chi-square tests. The results showed that the role of midwives was significantly associated with an increase in adolescents' knowledge (r = 0.579; p = 0.0008). However, no relationship was found between the role of midwives and adolescent attitudes (r = 0.264; p = 0.158). Regarding the variable of intention, all respondents (100%) expressed a desire to delay marriage until the age of ≥ 20 years, so statistical analysis could not be performed. These findings confirm that midwife education is effective in increasing adolescent knowledge, but changes in attitudes and intentions are influenced by other social factors that have been established previously. A collaborative approach between midwives, families, and schools is needed to strengthen comprehensive prevention of early marriage.